Радіаційні характеристики клімату Західної України: можливості ідентифікації змін. Фізична географія та геоморфологія - Холявчук, Дарія Іванівна (Фізична географія та геоморфологія., 2019)
The study aims at identifying possibilities for identification of short-term climate changes using satellite observations. For these purposes, Surface Solar Radiation Data Set - Heliosat (SARAH-2) of the EUMETSAT agency is applied. Gridded monthly and annual data of surface solar radiation in the years 1983-2015 are used to detect regional radiation variability in Western Ukraine. The flat and mountainous territory of Western Ukraine is found an appropriate example to detect changes while being the topography complex surface where the radiation characteristics are transformed. Accordingly, here solar surface radiation serves an indicator of atmospheric circulation peculiarities. Spatial distribution of mean and trend characteristics is addressed. Results confirm the appropriateness of the satellite-based climate data record of the solar surface irradiance SARAH-2 to detect decadal variability of solar surface radiation. The trends are the most precise in the summer half of the year and the least – in the winter months over the mountain and high hilly terrains. Spatial distribution of radiation values witness not only of latitude and longitude nature patterns but of local and mesoclimatic peculiarities related to geometrical and physical features of surfaces. Even in the annual context, differences in the solar surface radiation over mountain ridges, mountain foothills with distinctive exposition, hilly terrains with altitudes over 300 m, and depression forms are distingushed. The trend plots are also suggested as the potential option to detect climate changes at regional and local levels. In the winter months, because of high albedo of snow surfaces and the data over mountain massifs with different slope surfaces, radiation values maybe overestimated. Accordingly, their further application should involve a reliability assessment. Insufficient spatial differences on the trend maps contribute to the future comparative study of areas with specific radiation features while using in situ actinometrical measurements.
Solar radiation characteristics of the climate of Western Ukraine: potential for identification of changes
Keywords: Solar surface radiation, satellite climatological data, linear trends, mountain and flat surfaces